Sunday morning in Maine - Sample, Tim. ([New York] : CBS News, 1996)
A collection of the very best "Postcards from Maine" as originally broadcast on CBS Sunday Morning.
Growing up Boothbay Harbor -- The Jonesport lobster boat race -- Cindy Blodgett fever -- Mud season -- Urchin diving -- Cranberry Island graduation -- Robert McCloskey's world -- Potato harvest in "The County" -- The Shakers -- Common ground fair -- Wreathing downeast -- Elliot Winslow's Christmas.
Producer, Mary Lou Teel.
VHS.
Keywords: Maine -- Social life and customs; Maine -- Description and travel